Therapeutic effects of total saikosaponins from Radix bupleuri against Alzheimer’s disease - Li, Juan; Zou, Bin; Cheng, Xiao-Yu; Yang, Xin-He; Li, Jia; Zhao, Chun-Hui; Ma, Rui-Xia; Tian, Ji-Xiang; Yao, Yao (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disease characterized by memory loss and cognitive dysfunction in the elderly, with amyloid-beta (Aβ) deposition and hyperphosphorylation of tau protein as the main pathological feature. Nuclear factor 2 (Nrf2) is a transcription factor that primarily exists in the cytosol of hippocampal neurons, and it is considered as an important regulator of autophagy, oxidative stress, and inflammation. Total saikosaponins (TS) is the main bioactive component of Radix bupleuri (Chaihu). In this study, it was found that TS could ameliorate cognitive dysfunction in APP/PS1 transgenic mice and reduce Aβ generation and senile plaque deposition via activating Nrf2 and downregulating the expression of β-secretase 1 (BACE1). In addition, TS can enhance autophagy by promoting the expression of Beclin1 and LC3-II, increasing the degradation of p62 and NDP52 and the clearance of phosphorylated tau (p-tau), and reducing the expression of p-tau. It can also downregulate the expression of nuclear factor-κB (NF-κB) to inhibit the activation of glial cells and reduce the release of inflammatory factors. In vitro experiments using PC12 cells induced by Aβ, TS could significantly inhibit the aggregation of Aβ and reduce cytotoxicity. It was found that Nrf2 knock-out weakened the inhibitory effect of TS on BACE1 and NF-κB transcription in PC12 cells. Moreover, the inhibitory effect of TS on BACE1 transcription was achieved by promoting the binding of Nrf2 and the promoter of BACE1 ARE1. Results showed that TS downregulated the expression of BACE1 and NF-κB through Nrf2, thereby reducing the generation of Aβ and inhibiting neuroinflammation. Furthermore, TS could ameliorate synaptic loss and alleviate oxidative stress. In gut microbiota analysis, dysbiosis was demonstrated in APP/PS1 transgenic mice, indicating a potential link between gut microbiota and AD. Furthermore, TS treatment reversed the gut microbiota disorder in APP/PS1 mice, suggesting a therapeutic strategy by remodeling the gut microbe. Collectively, these data shows that TS may serve as a potential approach for AD treatment.